Citizen journalism role in promoting cultural integration and peace in Malaysia - Mahamed, Mastura; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2017)
Multi ethnicity and diverse cultures have shape Malaysia. Malaysians in recent years have adopted the new communication and media technologies to initiate virtual interaction and discussion in many topics cross cultural and ethnic backgrounds with the emerging ICT and internet infrastructure, the potential to promote cultural integration and peace are endless. The role of citizen journalism reflected this potential. They found to use the internet and new media platforms to create alternative space for news on the cyberspace to express multiple viewpoints in issues relating to cultural integration and unity which is something considered sensitive in multiracial society like Malaysians. The new media platform has made the Internet becoming more interactive thus create an alternative platform to discuss cross cultural and integration issues that often being shun away by the mainstream media. Today, thousands of citizen journalism blogs and citizen journalism has evolved in line with accessibility and growth of these technologies. This is reflected in the society by providing instant networking and expanding the space for people from different cultures existed in harmony and integration into the diverse society. The purpose of this paper is to analyse to what extent citizen journalism does contribute in promoting cultural integration among Malaysians. Based on analysing previous literatures, it is found that citizen journalism has influence cultural integration and peace yet the evidence is yet to be examine in Malaysian context. It is interesting to see if the contribution of citizen journalism in Malaysia potentially plays a more significant role in promoting cultural integration and peace among Malaysians.